The Effectiveness of the Inquiry Learning Model on Increasing Students' Interest in Learning Economics - Fitriyuningsih Fitriyuningsih; Sigit Santoso; Kristiani Kristiani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the effectiveness of the inquiry learning model in increasing student interest in learning economics. This study was conducted at SMA Negeri 3 Wera. This research is experimental research with one group pretest-posttest design. The research sample was students of class XI IPS 2, totaling 26 students were been selected through cluster random sampling technique from 4 classes. The research sample was taught using the inquiry model. The data collection technique is non-test, namely using a learning interest questionnaire. Data analysis used paired samples test with the help of SPSS 22 software. The questionnaire results on student interest in learning obtained a mean pretest percentage of 48.91% (low) and 66.76% posttest (high). The data analysis results obtained sig. < 0.05. It means that there are differences in students' interest in learning economics between before and after learning. The results of this study indicate an increase in student interest in learning economics. So, the inquiry learning model effectively increases students' interest in learning economics.